2022
DOI: 10.3390/life12060815
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Sarcopenia on Cholangiocarcinoma

Abstract: Sarcopenia is considered an important factor affecting the prognosis of cancer patients. Only complete surgical resection confers the chance of curing cholangiocarcinoma with sarcopenia. However, the prognosis is poor, even for patients who undergo surgical resection. Data from 13 trials of patients with sarcopenia and intrahepatic cholangiocarcinoma (ICC) or perihilar cholangiocarcinoma (PHC) were collected and reviewed. During all trials, sarcopenia was assessed using the psoas muscle or total skeletal muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
1
2
0
Order By: Relevance
“…Our findings also support those of previous studies, as we showed that sarcopenia was associated with increased operation time, intraoperative blood loss, packed RBC transfusion, and poor overall short-term prognosis ( 29 , 39 ). Moreover, sarcopenia showed poor OS which was consistent with findings of previous studies, while we did not observe any relevance to RFS ( 38 ). It can be interpreted that our cut-off was based on the ROC curve analysis of ICU admission.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings also support those of previous studies, as we showed that sarcopenia was associated with increased operation time, intraoperative blood loss, packed RBC transfusion, and poor overall short-term prognosis ( 29 , 39 ). Moreover, sarcopenia showed poor OS which was consistent with findings of previous studies, while we did not observe any relevance to RFS ( 38 ). It can be interpreted that our cut-off was based on the ROC curve analysis of ICU admission.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, frequent obstructive jaundice in patients with Klatskin tumors makes them vulnerable to poor oral intake and decreased activity, which consequently induce sarcopenia ( 36 , 37 ). Among many previous definitions, the cut-offs for diagnosing sarcopenia for Klatskin tumor differed depending on the studies (range of PMI cut-off for men: 4.77 – 8.60 cm²/m² and for women: 3.38 – 6.04 cm²/m²) ( 38 ). We used the normalised PMA which is widely used to diagnose sarcopenia, and the cut-off value was determined by ROC curve analysis by taking the rate of ICU admission as an indicator for predictive validity to determine the optimal cut-off value for each sex (6.74 cm²/m² for men and 3.39 cm²/m² for women).…”
Section: Discussionmentioning
confidence: 99%
“…Hilar cholangiocarcinoma is the main type of extrahepatic cholangiocarcinoma, accounting for 58% to 75% [ 19 , 20 ]. Due to the special location of the disease and the characteristics of early invasion of blood vessels, nerves, lymphoid tissues and adjacent liver tissues, the operation for hilar cholangiocarcinoma is more difficult and complex [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%